Student Employment and Education: A Meta-Analysis - Katerina Kroupova; Tomas Havranek; Zuzana Irsova (ZBW - Leibniz Information Centre for Economics, 2021)
Educational outcomes have many determinants, but one that most young people can readily control is choosing whether to work while in school. Sixty-nine studies have estimated the effect, but results vary from large negative to positive estimates. We show that the results are systematically driven by context, publication bias, and treatment of endogeneity. Studies ignoring endogeneity suffer from an upward bias, which is almost fully compensated by publication selection in favor of negative estimates. Net of the biases, the literature suggests a negative but economically inconsequential mean effect. The effect is more negative for high-intensity employment and educational outcomes measured as decisions to dropout, but it is positive in Germany. To derive these results we collect 861 previously reported estimates together with 32 variables reflecting estimation context, use recently developed nonlinear techniques to correct for publication bias, and employ Bayesian and frequentist model averaging to assign a pattern to the heterogeneity in the literature.
Keywords: C83; I21; J22; 330; Student employment; educational outcomes; meta-analysis; publication bias; Bayesian model averaging